Teachers of the faith and the future the life and works of B.W. Newton and Dr S. P. Tregelles - Newton, Benjamin Wills, 1807-1899; Tregelles, Samuel Prideaux, Dr, 1813-1875; Fromow, George H. (London, UK Sovereign Grace Advent Testimony, 1969)
Includes indexes.
Keywords: Newton, Benjamin Wills, -- 1807-1899, -- Brethren movement, teacher, -- biography; Tregelles, Samuel Prideaux, -- Dr, -- 1813-1875 -- Brethren movement, teacher, -- biography; Brethren movement -- history -- biography